Building an e-Commerce Infrastructure in Jordan: Challenges and Requirements - Al-Shboul, Muhannad Anwar; Alsmadi, Izzat Mahmoud (International Journal of Interactive Mobile Technologies (iJIM), 2010)
Many countries around the world are trying to build and enhance their internet infrastructure and utilize services related to the Internet such as e-Commerce, information connectivity, accessibility, etc. However, studies indicated that network and hardware requirements are not always the major barrier for progressing in these goals. In some cases, cultural, legal or environmental factor may dominate the type of barriers for the expansion of internet related service in many countries around the world. This paper presents challenges and requirements for the enhancement of e-Commerce services in particular for Jordan.